THE ROLE OF USING COLLOCATIONS IN IMPROVING ENGLISH FLUENCY (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article provides information about English collocations, types, grammatical categories, examples and distinctions between strong, weak and fixed collocations. Furthermore, benefits of using collocations in different contexts to be more fluent speaker is explicitly clarified.